Front Cover Picture: From Peripheral Stereogenic Center to Axial Chirality: Synthesis of 3‐Arylthiophene Atropisomers (Adv. Synth. Catal. 4/2023). Issue 4 (19th January 2023) - Li, Lin; Xi, Junwei; Hong, Biqiong; Gu, Zhenhua
Abstract : The front cover picture illustrates the palladium‐catalyzed the chirality transfer from peripheral stereogenic carbon center to axial chirality starting from 8 H ‐indenothiophen‐8‐ols. The process is different from traditional point‐to‐axial chirality transfer aromatization reaction of a non‐aromatic intermediate, in which the new created chiral axis is usually directly attach to a stereogenic centers. This reaction provides an easy way to access highly functionalized 3‐arylthiophene atropisomers in high enantioselectivity. Details can be found in the Update by Junwei Xi, Zhenhua Gu and co‐workers (L. Li, J. Xi, B. Hong, Z. Gu, Adv. Synth. Catal . 2023, 365, 594–599; DOI: 10.1002/adsc.202200957 ).